2011
DOI: 10.1021/ac103155f
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide Array-in-Well Platform for Detection and Genotyping Human Adenoviruses by Utilizing Upconverting Phosphor Label Technology

Abstract: We have developed a robust array-in-well test platform based on an oligonucleotide array, combining advantages of simple instrumentation and new upconverting phosphor reporter technology. Upconverting inorganic lanthanide phosphors have a unique property of photoluminescence emission at visible wavelengths under near-infrared excitation. No autofluorescence is produced from the sample or support material, enabling a highly sensitive assay. In this study, the assay is performed in standard 96-well microtiter pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 32 publications
0
38
0
2
Order By: Relevance
“…Die Gruppe von Soukka [206][207][208] [209] 9. Durch Mikrosphären codierte heterogene Assays Die Mikrotiterplatte als Festphase für Immunassays kann durch Mikrosphären ersetzt werden, und suspendierte Mikrosphären kçnnen durch Durchflusszytometrie sortiert oder in Femtoliterarrays eingeordnet werden, wie in der Einleitung beschrieben.…”
Section: H H Gorris Und O S Wolfbeisunclassified
“…Die Gruppe von Soukka [206][207][208] [209] 9. Durch Mikrosphären codierte heterogene Assays Die Mikrotiterplatte als Festphase für Immunassays kann durch Mikrosphären ersetzt werden, und suspendierte Mikrosphären kçnnen durch Durchflusszytometrie sortiert oder in Femtoliterarrays eingeordnet werden, wie in der Einleitung beschrieben.…”
Section: H H Gorris Und O S Wolfbeisunclassified
“…Ylihärsilä et al [136] demonstrated genotyping of ten common adenovirus genotypes with an array-in-well platform and validated the assay with clinical samples. Eleven selective probe spots (diameter 375 μm) in three replicas and positive control oligonucleotide spots were printed on the bottom of standard microtiter wells.…”
Section: Array-type Multiplexed Assaysmentioning
confidence: 99%
“…OraSure Technologies, Inc. (former STC Technologies; Pennsylvania, USA) with its research partners SRI International (California, USA) and Leiden University Medical Center (the Fig. 6 Array-in-well platform for qualitative genotyping based on hybridization patterns [136]. The DNA probes were spotted in three replicas together with control spots in the corners.…”
Section: Lateral Flow Testsmentioning
confidence: 99%
See 2 more Smart Citations